2020
DOI: 10.1007/s10620-020-06326-y
|View full text |Cite
|
Sign up to set email alerts
|

There Is a Great Future in Plastics: Personalized Approach to the Management of Hilar Cholangiocarcinoma Using a 3-D-Printed Liver Model

Abstract: In recent years, three-dimensional (3-D) printing technology has become a standard tool that is used in several medical applications such as education, surgical training simulation and planning, and doctor-patient communication. Although liver surgery is ideally complemented by the use of pre-operative 3-D-printed models, only a few publications have addressed this topic. We report the case of a 29-year old Caucasian woman admitted for a Klatskin tumor infiltrating the right portal vein requiring surgery that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…It is currently not possible to generalise findings to inform 3DPLM-LCR practice; however, clear themes emerge in this review that may have explanatory power concerning 3DPLMs' utility in LCR, which may motivate future research efforts to rigorously evaluate the impact of 3DPLMs on LCR patients' outcomes. The 16 criteria listed above were scored for each article based on the degree to which that article met those criteria, as outlined by Sirriyeh et al [40]. 0 = Not at all, 1 = Very slightly, 2 = Moderately, 3 = Completely.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is currently not possible to generalise findings to inform 3DPLM-LCR practice; however, clear themes emerge in this review that may have explanatory power concerning 3DPLMs' utility in LCR, which may motivate future research efforts to rigorously evaluate the impact of 3DPLMs on LCR patients' outcomes. The 16 criteria listed above were scored for each article based on the degree to which that article met those criteria, as outlined by Sirriyeh et al [40]. 0 = Not at all, 1 = Very slightly, 2 = Moderately, 3 = Completely.…”
Section: Resultsmentioning
confidence: 99%
“…These articles' references were examined to identify five secondary articles [12,14,[37][38][39]. One further article was identified serendipitously during a manual search [40]. Altogether, 22 articles were identified for inclusion in the review (Figure 1).…”
Section: Article Identification Screening and Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The merits of the application of XR techniques to surgical support include no need for a sterilized display monitor, better spatial awareness, and the ability to share 3D images among all surgeons. 24 XR techniques are applied to preoperative planning or visualization of vessels in liver surgery, 25 , 26 , 27 and XR images are suitable for clinical presentation because of their sharing function. Huettl et al 25 compared 3D printed liver models and VR liver models and concluded that 3D VR liver models enable a better and partially faster anatomical orientation than 3D printed liver models.…”
Section: Preoperative Simulationmentioning
confidence: 99%
“…Especially in VR, the surgeons can be immersed in the patient's own liver. The merits of the application of XR techniques to surgical support include no need for a sterilized display monitor, better spatial awareness, and the ability to share 3D images among all surgeons 24 . XR techniques are applied to preoperative planning or visualization of vessels in liver surgery, 25‐27 and XR images are suitable for clinical presentation because of their sharing function.…”
Section: Preoperative Simulationmentioning
confidence: 99%